1998
DOI: 10.1097/00007632-199805150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation Does Not Alter the Position of the Sacroiliac Joint

Abstract: Manipulation of the sacroiliac joint normalized different types of clinical test results but was not accompanied by altered position of the sacroiliac joint, according to roentgen stereophotogrammetric analysis. Therefore, the positional test results were not valid. However, the current results neither disprove nor prove possible beneficial clinical effects achieved by manipulation of the sacroiliac joint. Because the supposed positive effects are not a result of a reduction of subluxation, further studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 28 publications
4
59
0
2
Order By: Relevance
“…22 When applied, spinal manipulative therapy forces are not specific to intended location, 21 vary greatly from practitioner to practitioner, 18 despite similar therapeutic effects, and do not result in measurable changes in joint position. 23 Clinical A patient with complaints of focal low back pain is evaluated by a physical therapist. The physical therapist notes no contraindications to the use of spinal manipulative therapy and applies an appropriately directed technique to the low back.…”
Section: What Should Be the Response?mentioning
confidence: 99%
“…22 When applied, spinal manipulative therapy forces are not specific to intended location, 21 vary greatly from practitioner to practitioner, 18 despite similar therapeutic effects, and do not result in measurable changes in joint position. 23 Clinical A patient with complaints of focal low back pain is evaluated by a physical therapist. The physical therapist notes no contraindications to the use of spinal manipulative therapy and applies an appropriately directed technique to the low back.…”
Section: What Should Be the Response?mentioning
confidence: 99%
“…In our opinion, mechanical forces are not solely responsible for these observations, but rather neurophysiological control processes are also affected. Tullberg et al (1998) demonstrated that PA may be eliminated manually with no significant change in sacroiliac joint position. According to these authors, a mechanical force directed to the pelvis is only a source of input information to the control system, where it produces a specific 're-set' feature, and reexecutes a symmetrical tension pattern, which is observed in the activity of effectors.…”
Section: Discussionmentioning
confidence: 97%
“…There is growing evidence that movement of the SI joint is so small that detecting subtle differences may be extremely difficult if not impossible. [76][77][78] Furthermore, using roentgen stereophotogrammetric analysis, Tullberg et al 80 found that spinal manipulation did not alter the position of the SI joint. These results suggest that the theoretical foundation for bony movement-upon which many of the traditional tests are based-even if reliably measured, may be seriously flawed.…”
Section: Discussionmentioning
confidence: 99%